2014
DOI: 10.1590/1414-431x20133221
|View full text |Cite
|
Sign up to set email alerts
|

VEGF receptor expression decreases during lung development in congenital diaphragmatic hernia induced by nitrofen

Abstract: Changes in vascular endothelial growth factor (VEGF) in pulmonary vessels have been described in congenital diaphragmatic hernia (CDH) and may contribute to the development of pulmonary hypoplasia and hypertension; however, how the expression of VEGF receptors changes during fetal lung development in CDH is not understood. The aim of this study was to compare morphological evolution with expression of VEGF receptors, VEGFR1 (Flt-1) and VEGFR2 (Flk-1), in pseudoglandular, canalicular, and saccular stages of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
(48 reference statements)
1
19
0
1
Order By: Relevance
“…As there is a limitation of how to differentiate nitrofen fetuses with and without hernia before sacrifice without a special ultrasound to small animals, we had to use a volume that did not overload the lungs of CDH fetuses, but could also properly expand and ventilate the lungs of the N-fetuses. Losty et al evaluated the static lung compliance in fetuses with CDH and normal rats, and observed a decrease in compliance in the exposed fetuses and, in particular, in fetuses with CDH 26 , justifying the need for a smaller volume in group N. These results also corroborate the findings of a recent study from our group, which showed lower lung volume and air space in CDH fetuses 27 . After the passage of the learning curve, the success rate in ventilation of C fetuses was efficient, whereas in fetuses of group N the learning curve was longer and the success rate of ventilation was lower.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 89%
“…As there is a limitation of how to differentiate nitrofen fetuses with and without hernia before sacrifice without a special ultrasound to small animals, we had to use a volume that did not overload the lungs of CDH fetuses, but could also properly expand and ventilate the lungs of the N-fetuses. Losty et al evaluated the static lung compliance in fetuses with CDH and normal rats, and observed a decrease in compliance in the exposed fetuses and, in particular, in fetuses with CDH 26 , justifying the need for a smaller volume in group N. These results also corroborate the findings of a recent study from our group, which showed lower lung volume and air space in CDH fetuses 27 . After the passage of the learning curve, the success rate in ventilation of C fetuses was efficient, whereas in fetuses of group N the learning curve was longer and the success rate of ventilation was lower.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 89%
“…After cleaning, the newborn pups were positioned on a heated table where they were intubated with an intravascular de Teflon 24G Vialon TM catheter (BD Insyte Autoguard, Becton-Dickinson Infusion Therapy System Inc., Sandy, UT, USA), with a continuous 100 % oxygen (O 2 ) flow with cycling frequency of 80 breaths per minute (bpm), FiO 2 1.0, I:E ratio of 1:1, PEEP of 0 cm H 2 O for 30 min. We calculated a tidal volume of *13.5 mL/kg in C fetuses (75 lL) based on our previous studies on lung volume [16] greater than the volume used by Kroon et al [17] but with a lower cycling frequency (80 bpm). The CDH fetuses were ventilated with 50 lL, because a high incidence of pneumothorax was observed when ventilating with 75 lL in a pilot study.…”
Section: Harvest Of Fetuses For Ventilationmentioning
confidence: 99%
“…VEGF, a modulator of pulmonary angiogenesis, endothelial cell proliferation, and permeability of the vessels, 18 participates in pulmonary development and induces conversion of glycogen into surfactant in type II pneumocytes. 19,20 Plasma VEGF levels were found elevated and correlated with clinical severity of pulmonary vascular disease in infants with CDH. 21 Furthermore, the authors report a most obvious pattern of increased VEGF in the first week of life in CDH patient, who did not survive and postulate a critical early postnatal period in VEGF-mediated pulmonary vascular development.…”
Section: Discussionmentioning
confidence: 98%